Studi Pengembangan Air Terjun Tibu Sampi Sebagai Daya Tarik Wisata Di Kabupaten Tabanan - Dewi, Gek Ayu Tahta Kurnia Natha; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA, 2019)
Tibu sampi waterfall is a waterfall that has the potentiality and opportunities to be developed into a tourist attraction. However, the development of this waterfall has not been optimally reached. This study aims to determine the development of Tibu Sampi Waterfall as a tourist attraction. This study uses qualitative data with data sources in the form of primary data and secondary data. Data sources are obtained through observation, interview and documentation techniques with the technique of determining individual sample selection. The results of this study indicate that there are internal and external obstacles in the development of Tibu Waterfall as a tourist attraction. The internal obstacles are divided into three, namely the limited capital owned by Gunung Salak village; lack of adequate human resources in the field of tourism; and lack of promotion in the development of tourist attractions. The external obstacle is lack of contributions from investors.  Of the various obstacles faced and slowing down the development of Tibu Waterfall as a tourist attraction, the community must create several efforts including the government or related parties to provide tourism education and training to the local community; to improve tourism products; to disseminate information in the form of brochures and guidebooks; to improve structuring and infrastructure; to cooperate with investors; to make local culture an attraction for tourists;  and to develope tour packages.    Keywords : Study of development, tourist attraction, Gunung Salak Village, Tibu Sampi Waterfall